Pemertahanan Bahasa Jawa Dialek Tegal dalam Kumpulan Cerkak Tegalan Warung Poci Karya Dr. Maufur - Ningtyas, Siska Aditya; Astuti, Eka Yuli; M.Pd., Widodo (Sutasoma : Jurnal Sastra Jawa, 2019)
This study aims to describe the forms of retention of the Javanese language in the Tegal dialect in the cerkak of Tegalan Warung Poci by Dr. Maufur. This research produces forms of retention of Javanese Tegal dialect, namely forms of active language retention and forms of passive language retention by recording it on a data card. Forms of active language retention in the form of the use of words with Tegal dialect that are rarely used in daily life include: basic word forms, forms of affixed words, forms of reduplication, forms of reduplication with implications, and forms of clay saroja. The passive language retention form shows the use of foreign language elements in fragments of Tegal dialect which includes the use of basic words, affixed words, phrases, reduplication, affixed reduplication, and translation of foreign language words (Indonesian and English) into the Tegal dialect that refers to language error or interference. The translation shows that the Tegal dialect is dynamic because it raises elements of the foreign language in the sentence fragment with the aim of creating communicative sentences and giving a different color to the use of the Tegal dialect.Keyword: language maintenance; Tegal dialect; Warung Poci